Preparation and characterization of a novel solid polymer electrolyte based on lithium hexafluoroarsenate - Silva, Maria Manuela (2004)
In this article the results of a study of a new solid polymer electrolyte based onpoly(trimethylene carbonate), henceforth designated as p(TMC), and lithium hexafluoroarsenate are described. Samples of electrolytes with different salt contents were prepared by solventcasting from tetrahydrofuran and characterized by conductivity measurements and thermal analysis using DSC and TGA. The salt content of these electrolytes was identified by theconventional notation based on the polymer/salt ratio. In accordance with this notation the value of n represents the number of ((C=O)OCH2CH2CH2O) units per lithium ion.The appearance and morphology of electrolyte samples with compositions of n between 4 and 80 was similar to that observed with electrolytes based on the same host polymer with other lithiumsalts. Over this composition range thin films of electrolyte were transparent, free-standing and completely amorphous.